Comparison of plant secondary metabolites and digestibility of three different boreal coniferous trees - Stolter, Caroline; Niemelä, Pekka; Ball, John P.; Julkunen-Tiitto, Riitta; Vanhatalo, Aila; Danell, Kjell; Varvikko, Tuomo; Ganzhorn, Jörg U. (Basic and Applied Ecology, 2009)
v 2009 ok